2013
DOI: 10.1179/2045772313y.0000000142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of electromyostimulation on muscle and bone in men with acute traumatic spinal cord injury: A randomized clinical trial

Abstract: Objective: To study the effect of 14 weeks of electromyostimulation (EMS) training (47 minutes/day, 5 days/ week) on both muscle and bone loss prevention in persons with recent, complete spinal cord injury (SCI). Design: Prospective, experimental, controlled, single-blind randomized trial with external blind evaluation by third parties. Methods: Eight men with recent SCI (8 weeks from injury; ASIA Impairment Scale (AIS) "A") were randomized into the intervention or the control groups. Cross-sectional area of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 44 publications
1
45
0
3
Order By: Relevance
“…Most studies have failed to find an effect of various exercise loading protocols on leg bone in SCI . However, our results support the few previous studies that found high exercise volume (magnitude × frequency) effective in improving bone health.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Most studies have failed to find an effect of various exercise loading protocols on leg bone in SCI . However, our results support the few previous studies that found high exercise volume (magnitude × frequency) effective in improving bone health.…”
Section: Discussionsupporting
confidence: 78%
“…Bone remodels continuously in response to applied stresses and strains, and these adaptations are central to maintain bone mass and ensure sufficient bone strength. However, interventions that load sublesional bone in SCI (eg, standing frame, body‐weight‐supported treadmill walking, functional electrical stimulation‐ [FES‐] cycling) have rarely been shown to have even a modest effect, if any effect at all . This could be because of insufficient loading intensity (magnitude, number of cycles, and duration) to promote changes in bone density.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral effects of NMES include increase in contractile force and fatigue resistance, 78,79 increase in muscle mass, 80 reduction of edema, 81 conversion of fast-twitch fast-fatiguing glycolytic type II muscle fibers to slow-twitch fatigue-resistant oxidative type I muscle fibers, 79 and enhanced hyperemic arterial response and endothelium-dependent cutaneous vasodilation. 82 These peripheral effects can reverse disuse atrophy and may explain in part some improvements stroke patients experience after various NMES treatments.…”
Section: Peripheral and Central Effects Of Nmes In Stroke Rehabilitationmentioning
confidence: 99%
“…Intuitively, this appears to be a reasonable goal, since as muscles accelerate and decelerate body segments to oppose the pull of gravity, bones adapt in accordance with the forces exerted [1,4,[14][15][16]]. Yet while muscle's plasticity allows it to adapt to various loading paradigms, bone is far less responsive [3,20,34,55]. This impacts the ability of resistive exercise to abate bone losses in disuse models (e. g. space flight, osteoporosis, geriatrics, etc.)…”
Section: Introductionmentioning
confidence: 99%